Tindak Pidana Cyberstalking Ditinjau dari Undang-Undang Nomor 1 Tahun 2024 tentang Informasi dan Transaksi Elektronik (ITE) - Khusnul Latifah; Anita Zulfiani (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The development of information and communication technology has changed the pattern of human interaction, which was initially done face-to-face, to digital. The positive impact of internet usage is to facilitate connection and access to information, but it can also result in negative impacts such as cybercrime. The purpose of this research is to determine the crime of cyberstalking reviewed from Law Number 1 of 2024 concerning the Second Amendment to Law Number 11 of 2008 concerning Information and Electronic Transactions (ITE). This research is normative legal research that is prescriptive and uses a statutory approach, case approach, and conceptual approach. The collection of legal materials uses literature study techniques or document studies using syllogistic analysis techniques and using deductive thinking patterns. From the research, it was found that cyberstalking can be in the form of stalking followed by sexual harassment, privacy interference and continuous threats. In addition, cyberstalking is regulated in Law Number 1 of 2024 concerning Information and Electronic Transactions. However, this law has not been clearly or specifically regulated regarding stalking in the digital realm. Therefore, we need strict regulations regarding cyberstalking crimes.